2015
DOI: 10.1186/s12941-015-0063-7
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of CTX-M-type extended-spectrum beta-lactamase (ESBL)-producing nosocomial -Escherichia coli infection in China

Abstract: BackgroundEscherichia coli is one of the most common clinical pathogens causing nosocomial infection. The widespread cefotaxime-beta lactamases (CTX) has increased the multidrug resistance (MDR) of E. coli and has brought great trouble to the doctor treating the infection.MethodsESBL-positive E. coli isolates were collected from different hospitals in different areas and the minimal inhibitory concentration (MIC) was analyzed by the agar dilution method. The resistance gene types were detected using polymerase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 22 publications
4
20
4
Order By: Relevance
“…Our present investigation also confirmed that the isolates from Chennai were positive for group-1 and group-9 CTX-M. The CTX-M-group-1 was the most predominant ESBL detected in 19 isolates (95 % of ESBL) followed by group-9 and this was in accordance with another study, which detected bla CTX-M-1 and bla CTX-M-9 at 66.9 % (87/130) and 54.6 %(71/130) respectively, whereas none of the isolates in this study was positive for bla CTX-M-2 , bla CTX-M-8 and bla CTX-M-25 groups [30].…”
Section: Discussionsupporting
confidence: 92%
“…Our present investigation also confirmed that the isolates from Chennai were positive for group-1 and group-9 CTX-M. The CTX-M-group-1 was the most predominant ESBL detected in 19 isolates (95 % of ESBL) followed by group-9 and this was in accordance with another study, which detected bla CTX-M-1 and bla CTX-M-9 at 66.9 % (87/130) and 54.6 %(71/130) respectively, whereas none of the isolates in this study was positive for bla CTX-M-2 , bla CTX-M-8 and bla CTX-M-25 groups [30].…”
Section: Discussionsupporting
confidence: 92%
“…This is similar with the report from India, Germany, Malaysia, and Iran where the prevalence of coproduction of more than two types of beta-lactamases in inpatient was 70%, 77%, 50%, and 45% (5,8,11,13), respectively. These prevalences are lower in the report from China (11%), North Iran (30%), and Egypt (10%) (6,7,9).…”
Section: Discussioncontrasting
confidence: 41%
“…In recent years, the production of more than one beta-lactamase has frequently been reported in some countries, such as in the study from India (4,5), China (6), Iran (7), and Germany (8), Egypt (9), USA (10), Malaysia (11), and Bosnia and Herzegovina (B and H) (12). The antimicrobial resistance of Gram-negative bacteria has risen progressively during the past decades, leading to an increasing number of outbreaks due to the existence of multi-resistant bacteria, especially those producing more than one beta-lactamase type (4).…”
Section: Introductionmentioning
confidence: 99%
“…A high prevalence and broad geographic distribution of CTX-M-producing E. coli and K. pneumonia nosocomial strains have been shown in Russia. The bla CTX -M type is the most common ESBL resistance gene in E. coli isolates in China, as most reports indicate [25]. β-lactamases of the CTX-M-1 cluster were the predominant CTX-M enzymes in both species.…”
Section: Discussionmentioning
confidence: 93%